Food and Drug Administration Safety Communication on the Use of Transvaginal Mesh in Pelvic Organ Prolapse Repair Surgery: The Impact of Social Determinants of Health. Issue 1 (January 2021) - Mao, Jialin; Chughtai, Bilal; Ibrahim, Said; Sedrakyan, Art
Abstract : Objective: This study was to examine the impact of the July 2011 Food and Drug Administration (FDA) safety communication on the use of transvaginal mesh in pelvic organ prolapse (POP) repair by patients' race and ethnicity. Methods: We conducted an observational cohort study of women undergoing POP repairs in 2008 to 2015 in New York State. We examined the changes in transvaginal mesh use in POP repairs before and after the FDA communication by patients' race and ethnicity. Piecewise logistic regression models were used to assess the trends of mesh use, adjusting for patient characteristics. We performed a subgroup analysis of the trends of transvaginal mesh use by racial groups, stratifying by patients' neighborhood socioeconomic status. Results: We included 49, 848 women (78% white, 7% black, and 15% Hispanic) with an average ± SD age of 60.2 ± 13.0 years. After the safety communication, the use of transvaginal mesh in POP repairs decreased among white women (odds ratio [OR], 0.45; 95% confidence interval [CI], 0.41–0.50) and African Americans (OR, 0.48; 95% CI, 0.35–0.67) but remained stable among Hispanic women (OR, 0.88; 95% CI, 0.70–1.11). Only in the subgroup of patients from high-income areas, there was a trend toward decreasing mesh use among Hispanic patients after 2011 (OR, 0.71; 95% CI, 0.49–1.04). Conclusions: The communications related to the safety of transvaginal mesh did not have an equal impact across racial groups. Mesh use decreased among white and African American women but not among Hispanic women after the 2011 FDA safety communication. Particular attention is warranted for patients from disadvantaged groups, especially low-income minorities, when disseminating medical device safety messages. Abstract : Supplemental digital content is available in the text.